Forest fires and geographical variables in the buffer zone of La Amistad International Park, Costa Rica (UNED Research Journal, 2025)
Introduction: Forest fires significantly affect ecosystems, altering vegetation, carbon cycles, and climate patterns. The buffer zone of La Amistad International Park (PILA), created in 1982 and declared a UNESCO Biosphere Reserve the same year, was recognized as a World Heritage Site in 1983. This region, particularly the Indigenous Territories of Ujarrás, Salitre, and Cabagra inhabited by the Bribri and Cabécar peoples, faces recurring forest fires. Objective: This study examines the spatial and temporal dynamics of forest fires in the PILA buffer zone and explores their relationship with geographical variables influencing fire occurrence. Methods: We analyzed satellite data from MODIS and VIIRS, geospatial information from GWIS and FIRMS, and local field data. Burned areas were mapped for the period 2012-2020, and key geographical factors, including elevation, slope, vegetation cover, and proximity to human settlements, were assessed. Results: The most extensive burned areas were located in Indigenous Territories, with Ujarrás experiencing the largest impact (24,617.52 hectares). Geographical factors, such as steep slopes and proximity to populated areas, significantly influenced fire ignition and spread. Hotspots of recurring fires were identified in Ujarrás, with moderate occurrences in Salitre and Cabagra. Conclusions: Satellite technology provided essential data on fire patterns and their influencing variables, enabling the development of targeted prevention and mitigation strategies to protect biodiversity and support Indigenous communities from La Amistad buffer zone.
Keywords: burned areas; MODIS; Indigenous Territories; slope; fire mitigation